1998
DOI: 10.1103/physrevb.57.862
|View full text |Cite
|
Sign up to set email alerts
|

Free energy and vibrational entropy difference between ordered and disorderedNi3Al

Abstract: We have calculated free energy and vibrational entropy differences in Ni 3 Al between its equilibrium ordered structure and a disordered fcc solid solution. The free energy and entropy differences were calculated using the method of adiabatic switching in a molecular-dynamics formalism. The path chosen for the free-energy calculations directly connects the disordered with the ordered state. The atomic interactions are described by embedded-atom-method potentials. We find that the vibrational entropy difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Finally, the A-atom potential might be useful for thermodynamic calculations of phase behavior involving random solution phases, but in this case small difference in free energy may not be negligible. For instance, the order-disorder free energy for Ni 3 Al has been calculated by Ravelo et al [18] as 0.089-0.083 eV per atom in the range 200-700 K. The free energy difference between the true solid solution and the "average atom" solid solution that we compute here is ∆A~11-14% of the above value. This difference is not too large, and is much smaller than the configurational entropy difference, but might have small consequences for predicted phase behavior.…”
Section: Discussion and Summarymentioning
confidence: 58%
See 1 more Smart Citation
“…Finally, the A-atom potential might be useful for thermodynamic calculations of phase behavior involving random solution phases, but in this case small difference in free energy may not be negligible. For instance, the order-disorder free energy for Ni 3 Al has been calculated by Ravelo et al [18] as 0.089-0.083 eV per atom in the range 200-700 K. The free energy difference between the true solid solution and the "average atom" solid solution that we compute here is ∆A~11-14% of the above value. This difference is not too large, and is much smaller than the configurational entropy difference, but might have small consequences for predicted phase behavior.…”
Section: Discussion and Summarymentioning
confidence: 58%
“…Specifically, the Hamiltonian H is parametrized by a scalar variable λ ∈ [0, 1] with H (0) being the system of interest and H (1) being the reference system. Following Skinner et al [17] and Ravelo et al [18], we use an "alchemical" transformation where atom types are transformed from the true elemental atoms to the A-atom at each atomic site via linear interpolation of the mass and the EAM potential. Specifically, for an atom site that is occupied by a type-X atom in the true random alloy, the mass and potential 0 100 200 300 400 500 600 700 3.52 functions are transformed as…”
Section: A Methodologymentioning
confidence: 99%
“…In some studies [8,9], the complexity of the first-principles approach was tackled by using a simplified model for the vibrational entropy based on the Debye-Gruneisen approximation. All of these results seem to indicate that vibrational effects can be non-negligible.Calculations of the vibrational entropy difference between disordered and ordered Ni 3 Al (hereafter denoted DS o!d vib ) has so far been performed using only the semiempirical embedded atom method (EAM) [10][11][12]. Although the specific result seems to depend somewhat on the EAM potential used, all authors found values between 0.1k B and 0.3k B , which corresponds to the range of values found experimentally.…”
mentioning
confidence: 99%
“…Calculations of the vibrational entropy difference between disordered and ordered Ni 3 Al (hereafter denoted DS o!d vib ) has so far been performed using only the semiempirical embedded atom method (EAM) [10][11][12]. Although the specific result seems to depend somewhat on the EAM potential used, all authors found values between 0.1k B and 0.3k B , which corresponds to the range of values found experimentally.…”
mentioning
confidence: 99%
See 1 more Smart Citation